2015
DOI: 10.1080/17470218.2014.970204
|View full text |Cite
|
Sign up to set email alerts
|

Avoid violence, rioting, and outrage; approach celebration, delight, and strength: Using large text corpora to compute valence, arousal, and the basic emotions

Abstract: Ever since Aristotle discussed the issue in Book II of his Rhetoric, humans have attempted to identify a set of "basic emotion labels". In this paper we propose an algorithmic method for evaluating sets of basic emotion labels that relies upon computed co-occurrence distances between words in a 12.7-billion-word corpus of unselected text from USENET discussion groups. Our method uses the relationship between human arousal and valence ratings collected for a large list of words, and the co-occurrence similarity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(93 citation statements)
references
References 50 publications
5
85
3
Order By: Relevance
“…Arousal judgments from the ANEW norms set (Bradley & Lang, 1999) correlated with those in the Warriner et al (2013) norms set at r = .76 (as compared to .95 for valence and .80 for dominance). Attempts at algorithmically extrapolating human judgments have likewise found that human judgments of arousal are much less predictable than other semantic measures (Hollis & Westbury, 2016;Mandera, Keuleers, & Brysbaert, 2015;Recchia & Louwerse, 2015;Westbury et al, 2015). These findings, along with the results of our analysis of the skip-gram model, suggest that the concept of arousal is not as clearly specified as a semantic construct.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Arousal judgments from the ANEW norms set (Bradley & Lang, 1999) correlated with those in the Warriner et al (2013) norms set at r = .76 (as compared to .95 for valence and .80 for dominance). Attempts at algorithmically extrapolating human judgments have likewise found that human judgments of arousal are much less predictable than other semantic measures (Hollis & Westbury, 2016;Mandera, Keuleers, & Brysbaert, 2015;Recchia & Louwerse, 2015;Westbury et al, 2015). These findings, along with the results of our analysis of the skip-gram model, suggest that the concept of arousal is not as clearly specified as a semantic construct.…”
Section: Discussionmentioning
confidence: 61%
“…For instance, the similarity of meaning between two words can be assessed by measuring the similarity between their co-occurrence vectors. Cooccurrence vectors contain enough information to pass tests for basic verbal ability (e.g., Landauer & Dumais, 1997), to accurately predict human judgments of valence and arousal (e.g., Hollis & Westbury, 2016;Mandera, Keuleers, & Brysbaert, 2015;Recchia & Louwerse, 2015;Westbury, Keith, Briesemeister, Hofmann, & Jacobs, 2015), and to account for behavioral effects of high-level lexical properties such as subjective familiarity (Westbury, 2014) and imageability (Westbury et al, 2013).…”
mentioning
confidence: 99%
“…Can we tentatively infer that EADs to words are determined by their associations to five basic emotions then (Westbury et al, 2014)? Figure 1 illustrating the decision tree data for Model 3 suggests an even simpler answer: to obtain 99% correct EADs, the model requires only two questions.…”
Section: Stepwise Modeling Approachmentioning
confidence: 99%
“…A valence value would thus be computed from (1) neural activation patterns distributed over the sensory-motor representations of a word’s referents ( experiential aspect) and (2) the linguistic company the words keep (Harris, 1951), i.e., the size and density of their context ( distributional aspect; Jacobs et al, 2015), as computationally modeled using co-occurrence statistics (Hofmann and Jacobs, 2014). In favor of this view, Westbury et al (2014) recently showed that valence ratings of words can be predicted by their associations to a selected set of emotion labels, derived from theories of basic emotions (cf. also Hofmann and Jacobs, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, future studies will focus on developing new indices of sentiment for inclusion in SEANCE and additional valence features. Such indices will be based on sentiment dictionaries that are currently available, those that become available over time (e.g., the Warriner norms; Warriner, Kuperman, & Brysbaert, 2013;Westbury, Keith, Briesemeister, Hofmann, & Jacobs, 2015), or previous dictionaries that are updated. We also plan to add valence features, as necessary, to examine discourse features such as intensification.…”
Section: Resultsmentioning
confidence: 99%